Pengaruh Metode Joyfull Learning Terhadap Prestasi Belajar Peserta Didik - Maisyaroh, Rizki; Nadiah, Nadiah (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
Monotonous teaching methods often create a negative perception of education, leading students to feel stressed, demotivated, and impacting their academic performance. The implementation of the Joyful Learning method in schools aims to enhance students' skills, creativity, enthusiasm, interest, and engagement in learning. This study uses a quantitative approach with survey questionnaires, observations, and documentation techniques, and analyzes the data using product moment correlation. The sample consists of 43 students from SMK Negeri 7 East Jakarta, selected through random sampling. The research instruments included 20 items for variables X (Joyful Learning) and Y (student learning achievement). The analysis results show a correlation coefficient (rxy) of 0.530, which is greater than the rt value at the 5% significance level (0.304) and the 1% significance level (0.393). Thus, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. These findings confirm that the Joyful Learning method has a significant effect on improving students' academic performance. The implications of this study provide positive impacts not only on individual students but also on the overall quality of education. With a more enjoyable learning method, education is expected to become a more meaningful and fulfilling experience for all parties involved.